Continuous surface modification of glass fibers in a roll-to-roll plasma-enhanced CVD reactor for glass fiber/polyester composites. (June 2019) - Cech, Vladimir; Marek, Ales; Knob, Antonin; Valter, Jan; Branecky, Martin; Plihal, Petr; Vyskocil, Jiri
Abstract: Plasma-enhanced chemical vapor deposition (PECVD) is a cost-effective and green process of plasma polymer synthesis that can be used as a gentle but powerful tool for the surface modification of fibers and retains their bulk properties. This paper introduces the notion of a compact and modular device consisting of low-pressure reactor segments that have a specialized function and are adapted for the continuous modification of fiber surface. A roll-to-roll device, designed on an industrial scale, with a PECVD reactor was used for continuous plasma pretreatment and plasma polymerization coating on 1600 glass fibers in a bundle, with the fibers used as reinforcements in a glass fiber/polyester composite. Optimization of the plasma-processing conditions allowed for the improvement of interfacial adhesion between the glass fibers and polymer matrix, resulting in an increase in the shear strength of the polymer composite by 14%, compared to industrially sized fibers coated by wet chemical processes.